PENGARUH PEMBERIAN KOMPRES PARUTAN JAHE TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Imelda, Imelda; Suryani, Suryani; Farahdiba, Farahdiba (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Low back pain is a history of back pain that occurs so often in pregnancy that it is described as one of the minor disorders in pregnancy. Symptoms of pain usually occur between 4-7 months of pregnancy and the pain is usually felt in the lower back, sometimes spreading to the buttocks and thighs, and sometimes down to the legs (Herawati, 2017) Ginger compress is a non-pharmacological technique that can be applied to reduce pain in certain areas to meet the need for comfort and reduce or prevent muscle spasms. This study aims to see the effect of giving grated ginger compresses on lower back pain in third trimester pregnant women in the Jambi Kecil Community Health Center Working Area. The research method used a quasi-experiment and a pre-test and post-test one-group design to compare the results of interventions before and after giving grated ginger compresses to pregnant women in the third trimester who experienced lower back pain. The population in this study was 36 pregnant women in the third trimester in the working area of ​​the Jambi Kecil Community Health Center, and the total sample of pregnant women who experienced lower back pain was carried out in June 2023. Results of measuring lower back pain in third trimester pregnant women before applying compresses grated ginger in the Jambi Kecil Community Health Center Work Area in 2023, 30.6% experienced moderate pain and 39.4% experienced severe pain and after giving the grated ginger compress, 47.2% experienced mild pain and 52.8% experienced moderate pain. The conclusion of the research is that there is an effect of giving grated ginger compresses on reducing lower back pain in pregnant women in the third trimester in the Jambi Kecil Community Health Center working area.